An Otis Christmas - Long, Loren (Philomel Books, an Imprint of Penguin Group (USA) Inc., 2013)
On Christmas Eve at the farm, a horse faces complications while delivering her foal and Otis the tractor must race through snowy, treacherous woods to bring back Doc Baker before it is too late.